2023
DOI: 10.1080/07853890.2023.2166981
|View full text |Cite
|
Sign up to set email alerts
|

R-spondin family biology and emerging linkages to cancer

Abstract: The R-spondin protein family comprises four members (RSPO1-4), which are agonists of the canonical Wnt/β-catenin pathway. Emerging evidence revealed that RSPOs should not only be viewed as agonists of the Wnt/β-catenin pathway but also as regulators for tumor development and progression. Aberrant expression of RSPOs is related to tumorigenesis and tumor development in multiple cancers and their expression of RSPOs has also been correlated with anticancer immune cell signatures. More importantly, the role of RS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 82 publications
0
6
0
Order By: Relevance
“…Previous studies have shown that macrophages and dendritic cells are activated and positively correlated with ESCA progression [ 32 34 ], whereas resting mast cells are negatively correlated with ESCA progression [ 35 ]. Moreover, RSPO1 and RSPO3 expression exhibited significant correlations with immune checkpoint-related genes in various tumors [ 36 ], hinting at their potential for the development of immune checkpoint blockade therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that macrophages and dendritic cells are activated and positively correlated with ESCA progression [ 32 34 ], whereas resting mast cells are negatively correlated with ESCA progression [ 35 ]. Moreover, RSPO1 and RSPO3 expression exhibited significant correlations with immune checkpoint-related genes in various tumors [ 36 ], hinting at their potential for the development of immune checkpoint blockade therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Together with its ligand RSPO3, the LGR5 receptor promotes β-catenin signaling in cancer cells predominantly via membrane clearance of two endogenous negative regulators of β-catenin signaling: the transmembrane ubiquitin ligases ZNRF3 and RNF43 [17,21,31]. The fact that β-catenin signaling stimulates the colon cancer stem cell niche [32] explains why LGR5 has been recognized and used as a colon cancer stem cell marker [33].…”
Section: Discussionmentioning
confidence: 99%
“…These include Roof plate-specific spondins (R-spondins; RSPOs), Norrin, and Dickkopf (DKK), all of which are secreted proteins. R-spondins, consisting of four members (RSPO1-4), function as enhancers in the Wnt/β-catenin signaling pathway and are considered indispensable factors in carcinogenesis [ 58 ]. This effect was initially discovered in Xenopus embryos, and it was also observed that mouse R-spodin1-3 exhibits a similar effect [ 59 ].…”
Section: Overview Of the Wnt/β-catenin Signaling Pathwaymentioning
confidence: 99%